Overexpression of peanut (Arachis hypogaea L.) AhGRFi gene enhanced root growth inhibition under exogenous NAA treatment in Arabidopsis thaliana - Zhang, Zhou; Gangurde, Sunil S.; Chen, Songbin; Mandlik, Rushil Ramesh; Liu, Haiyan; Deshmukh, Rupesh; Xu, Jialing; Wu, Zhongkang; Hong, Yanbin; Li, Yin (Frontiers in Plant Science, 2023)
The 14-3-3 protein is a kind of evolutionary ubiquitous protein family highly conserved in eukaryotes. Initially, 14-3-3 proteins were reported in mammalian nervous tissues, but in the last decade, their role in various metabolic pathways in plants established the importance of 14-3-3 proteins. In the present study, a total of 22 14-3-3 genes, also called general regulatory factors (GRF), were identified in the peanut (Arachis hypogaea) genome, out of which 12 belonged to the ε group, whereas 10 of them belonged to the non- ε-group. Tissue-specific expression of identified 14-3-3 genes were studied using transcriptome analysis. The peanut AhGRFi gene was cloned and transformed into Arabidopsis thaliana. The investigation of subcellular localization indicated that AhGRFi is localized in the cytoplasm. Overexpression of the AhGRFi gene in transgenic Arabidopsis showed that under exogenous 1-naphthaleneacetic acid (NAA) treatment, root growth inhibition in transgenic plants was enhanced. Further analysis indicated that the expression of auxin-responsive genes IAA3, IAA7, IAA17, and SAUR-AC1 was upregulated and GH3.2 and GH3.3 were downregulated in transgenic plants, but the expression of GH3.2, GH3.3, and SAUR-AC1 showed opposite trends of change under NAA treatment. These results suggest that AhGRFi may be involved in auxin signaling during seedling root development. An in-depth study of the molecular mechanism of this process remains to be further explored.